Vibrational development of nanocomposite cylindrical shells by employing reduced graphene oxide (rGO) as a nanoscale strengthener - Sobhani, Emad; Safaei, Babak (Elsevier Sci Ltd, 2023)
This study uses the harmonic differential quadrature technique to learn more about the free vibration of cylinder constructions made from reduced graphene oxide nanocomposite (rGON). To support, using the Halpin-Tsai homogenization form, the effective Young's modulus related to the rGON is considered here. In addition, five distinct functionally graded (FG) distribution types of reduced graphene oxide (rGO) are examined along shell thickness. The main equations of the cylinder structures are identified by combining the first-order shear deformation theory (FSDT), the general shell theory, and Hamilton's principle. A comprehensive analysis of the impact of changing factors, such as rGO weight percent and FG distribution types, is presented. With the sig-nificant results: Regarding the rGON cylinder structure reinforced by uniformly rGO, adding 0.1%, 0.5%, 1%, and 2% rGO to the polymer matrix can cause to improving the minimum natural frequency to 1.91%, 9.23%, 17.75%, and 33.17% improvements compare with a cylindrical shell made by the pure polymer.
Keywords: Natural frequency; Reduced graphene oxide (RGO); Nanocomposite; Cylindrical Shells; Nano-reinforcement; GDQM